Potential Survival and Pathogenesis of a Novel Strain, Vibrio parahaemolyticus FORC_022, Isolated From a Soy Sauce Marinated Crab by Genome and Transcriptome Analyses - Chung, Han Y.; Lee, Byungho; Na, Eun J.; Lee, Kyu-Ho; Ryu, Sangryeol; Yoon, Hyunjin; Lee, Ju-Hoon; Kim, Hyeun B.; Kim, Heebal; Jeong, Hee G.; Kim, Bong-Soo; Choi, Sang H. (Frontiers in Microbiology, 2018)
Vibrio parahaemolyticus can cause gastrointestinal illness through consumption of seafood. Despite frequent food-borne outbreaks of V. parahaemolyticus, only 19 strains have subjected to complete whole-genome analysis. In this study, a novel strain of V. parahaemolyticus, designated FORC_022 (Food-borne pathogen Omics Research Center_022), was isolated from soy sauce marinated crabs, and its genome and transcriptome were analyzed to elucidate the pathogenic mechanisms. FORC_022 did not include major virulence factors of thermostable direct hemolysin (tdh) and TDH-related hemolysin (trh). However, FORC_022 showed high cytotoxicity and had several V. parahaemolyticus islands (VPaIs) and other virulence factors, such as various secretion systems (type I, II, III, IV, and VI), in comparative genome analysis with CDC_K4557 (the most similar strain) and RIMD2210633 (genome island marker strain). FORC_022 harbored additional virulence genes, including accessory cholera enterotoxin, zona occludens toxin, and tight adhesion (tad) locus, compared with CDC_K4557. In addition, O3 serotype specific gene and the marker gene of pandemic O3:K6 serotype (toxRS) were detected in FORC_022. The expressions levels of genes involved in adherence and carbohydrate transporter were high, whereas those of genes involved in motility, arginine biosynthesis, and proline metabolism were low after exposure to crabs. Moreover, the virulence factors of the type III secretion system, tad locus, and thermolabile hemolysin were overexpressed. Therefore, the risk of foodborne-illness may be high following consumption of FORC_022 contaminated crab. These results provided molecular information regarding the survival and pathogenesis of V. parahaemolyticus FORC_022 strain in contaminated crab and may have applications in food safety.